Perluasan Kompetensi Pengadilan Tata Usaha Negara dalam Mengadili Tindakan Faktual Pemerintah - Stephanie Angela Penu; Jeffry A. Ch. Likadja; Yohanes G. Tuba Helan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Decisions and decrees as legal instruments of the government in carrying out legal actions unilaterally, can be the cause of legal violations for citizens, in Law Number 5 of 1986 concerning State Administrative Courts and its amendments, the law explains that the object of state administrative disputes is that which contains legal actions that can have legal consequences for a person or civil legal entity, at least there is ease for the public to sue the government and request the cancellation of decisions made by the government, but due to the expansion of objects in Law Number 30 of 2014 Article 87 letter (a) includes written decisions, it also includes factual actions. Therefore, the problem formulation in this research is whether the state administrative court has the authority to adjudicate factual government actions that harm the community, how legal protection for people who are harmed by factual government actions. This research is a normative legal research with statutory, conceptual, historical, and doctrinal approaches that apply to determine the rule of law as a whole. The results showed that the expansion of the competence of the State Administrative Court to adjudicate factual actions of the government is not competent because it cannot cause legal consequences because it is not in line and contradicts what is regulated in Law Number 5 of 1986 concerning State Administrative Courts and its Amendments, the public does not get legal protection through the State Administrative Court as a result of the factual actions of State Administrative bodies/officials. Suggestions from this research are that factual actions should be removed or eliminated from the competence of the State Administrative Court and there is no need to expand the object of State Administrative disputes, for people who feel harmed by factual actions of State Administrative bodies/officials should file a lawsuit against the law to the district court.